Ultralow-noise headstage and main amplifiers for extracellular spike recording - Budai, Dénes (Acta Biologica Szegediensis, 2004)
This methodological paper provides a detailed description of a novel ultralow-noise pre- and main-amplifier system designed for the extracellular recording of voltage spikes produced by neuronal action potentials. The main difficulties with extracellular recording are the unwanted electrical signals that lower the recording quality. They include destructive interferences by alternating electric or magnetic fields, in addition to thermal and other random noises resulting from the intrinsic properties of the substances from which the electrode and the electrical circuit are made. The preamplifier is placed in a specially built metal headstage probe. It is designed so that microelectrodes can be plugged directly into the probe, keeping the electrode and preamplifier in the closest possible proximity. Unique electrode holder adaptors at the same time make the probe for the electrode holder with the added benefit of extended electrical shielding. The main amplifier contains tuned circuit band pass filters optimized for metal and carbon fiber microelectrodes. Electromagnetic interference pickup is reduced by the enclosing tin-plated iron box and a built-in 50/60 Hz reject filter. In test experiments, an excellent signal-to-noise ratio and low-noise baseline recording were achieved. When carbon fiber microelectrodes were applied in the medulla of anesthetized rats, the total peak-to-peak noise level of the system was about 25 µV, i.e., about 6 µV RMS, which is only a few µV higher than the theoretical random noise. It is concluded that, in combination with carbon fiber electrodes, the present amplifiers do not contribute significantly to the overall noise.